Canine symmetrical lupoid onychomadesis in bearded collies. Issue 5 (22nd July 2019) - Steimer, Tanja; Bauer, Alexander; Kienzle, Ellen; Mueller, Ralf S.
Abstract : Background: Symmetrical lupoid onychomadesis (SLO) is a disease not infrequently seen in bearded collie dogs in Germany. Objectives: The aim of this study was to compare historical and clinical data, as well as the mineral content of the hair and claws of bearded collies with SLO with that of normal control dogs. Animals: Twenty‐eight affected bearded collie dogs and 39 control dogs. Methods and materials: Owners completed an extensive questionnaire regarding upbringing, environmental conditions and diets. Claw specimens were obtained by claw trimming or gathering lost claws; hairs were obtained by plucking samples from several areas of the body; samples were converted to ash and evaluated in an atomic absorption spectrophotometer. Results: Clinical signs in affected dogs eventually involved all claws on all paws. In twelve dogs recurrence of onychomadesis was observed. There was no relevant association between gender, housing, diet and health management, physical stress and the development of SLO with exception of the age at which more intense exercise began. The most commonly used treatment combination was fatty acids, pentoxifylline and tetracycline; improvement occurred in 17 animals. Calcium, sodium and phosphorus concentrations were higher in the claws of affected dogs, whereas zinc concentrations were lower. The mineral content of hair samples of the affected dogs was not significantly different than controls. Conclusion and clinical importance: Symmetrical lupoid onychomadesis in bearded collies is clinically similar to what has been described in other breeds with regard to clinical signs and response to treatment. Early strenuous activity may increase the risk for disease occurrence in this breed. Abstract : Background –Symmetrical lupoid onychomadesis (SLO) is a disease not infrequently seen in bearded collie dogs in Germany.Objectives –The aim of this study was to compare historical and clinical data, as well as the mineral content of the hair and claws of bearded collies with SLO with that of normal control dogs.Conclusion and clinical importance –Symmetrical lupoid onychomadesis in bearded collies is clinically similar to what has been described in other breeds with regard to clinical signs and response to treatment. Early strenuous activity may increase the risk for disease occurrence in this breed. Résumé: Contexte: L'onychomadèse lupoïde symétrique (SLO) est une maladie rare chez le bearded collie en Allemagne. Objectifs: Le but de cette étude était de comparer les données cliniques et anamnestiques ainsi que le contenu minéral des poils et des griffes de bearded collie de Institute for Animal Nutrition and Dietetics/LMU Munich, atteints de SLO avec des chiens contrôles sains. Sujets: Vingt huit bearded collie atteints et 39 chiens contrôles. Matériels et méthodes: Les propriétaires ont rempli un questionnaire complet concernant l'éducation, les conditions environnementales et les régimes alimentaires. Les échantillons de griffe ont été obtenus par coupe de griffe ou récupération de griffes perdues; les poils ont été obtenus par prélèvement de plusieurs régions du corps; des échantillons ont été convertis en cendres et évaluées dans un spectrophotomètre d'absorption atomique. Résultats: Les signes cliniques des chiens atteints pouvaient atteindre toutes les griffes de toutes les pattes. Pour douze chiens, une récidive d'onychomadèse était observée. Il n'y avait pas d'association significative entre genre, habitat, alimentation et entretien, stress physique et le développement de SLO à l'exception de l'âge auquel un exercice intense était initié. L'association de traitements la plus fréquemment utilisée était acides gras, pentoxifylline et tétracycline; l'amélioration était observée pour 17 animaux. Les concentrations de calcium, sodium et phosphore étaient plus élevées dans les griffes des chiens atteints tandis que les concentrations de zinc étaient plus faibles. Le contenu minéral des échantillons de poils des chiens atteints n'était pas significativement différent des chiens contrôles. Conclusion et importance clinique: L'onychomadèse lupoïde symétrique chez le bearded collie est cliniquement identique à celle décrite dans les autres races concernant les signes cliniques et les réponses aux traitements. Une activité intense précoce peut augmenter le risque d'apparition de la maladie dans cette race. Resumen: Introducción: la onicomadesis lupoidea simétrica (SLO) es una enfermedad que se ve con relativa frecuencia en perros Bearded Collie en Alemania. Objetivos: el objetivo de este estudio fue comparar los datos históricos y clínicos, así como el contenido mineral del cabello y las uñas de Bearded Collies barbudos con SLO con el de perros control normales procedentes del Instituto de Nutrición Animal y Dietética/LMU Munich Animales: veintiocho perros Bearded Collie afectados y 39 perros control. Métodos y materiales: los propietarios completaron un extenso cuestionario sobre crecimiento, condiciones ambientales y dietas. Las muestras de uñas se obtuvieron cortándolas o recogiendo uñas perdidas; los pelos se obtuvieron arrancando muestras de varias áreas del cuerpo; las muestras se convirtieron en cenizas y se evaluaron en un espectrofotómetro de absorción atómica. Resultados: los signos clínicos en los perros afectados finalmente afectaron todas las uñas en todas las extremidades. En doce perros se observó recurrencia de onicomadesis. No hubo una asociación relevante entre el género, la vivienda, la dieta y el manejo de la salud, el estrés físico y el desarrollo de SLO, con excepción de la edad en que comenzó el ejercicio más intenso. La combinación de tratamiento más utilizada fue ácidos grasos, pentoxifilina y tetraciclina; se observó mejoría en 17 animales. Las concentraciones de calcio, sodio y fósforo fueron mayores en las uñas de los perros afectados, mientras que las concentraciones de zinc fueron menores. El contenido mineral de las muestras de pelo de los perros afectados no fue significativamente diferente de los controles. Conclusión e importancia clínica: la onicomadesis lupoidea simétrica en Bearded Collies barbudos es clínicamente similar a lo que se ha descrito en otras razas con respecto a los signos clínicos y la respuesta al tratamiento. La actividad vigorosa en edad temprana puede aumentar el riesgo de aparición de la enfermedad en esta raza. Zusammenfassung: Hintergrund: Die Symmetrische Lupoide Onychomadese (SLO) ist eine Erkrankung, die beim Bearded Collie in Deutschland nicht selten gesehen wird. Ziele: Das Ziel dieser Studie war ein Vergleich der anamnestischen und klinischen Daten sowie des Mineralgehalts von Haaren und Krallen am Institut für Tierernährung und Diätetik/LMU München zwischen Bearded Collies mit SLO und normalen Kontrollhunden. Tiere: Achtundzwanzig betroffene Bearded Collies und 39 Kontrollhunde. Methoden und Materialien: Die BesitzerInnen füllten einen ausführlichen Fragebogen in Bezug auf das Aufwachsen, die Umweltbedingungen und dem verabreichten Futter aus. Es wurden Krallenproben im Zuge des Krallenschneidens entnommen oder verlorene Krallen wurden eingesammelt; es wurden Haare durch Auszupfen an verschiedenen Stellen des Körpers entnommen; die Proben wurden in Asche umgewandelt und mittels Atomabsorptionsspektrometer evaluiert. Ergebnisse: Die klinischen Zeichen der betroffenen Hunde betrafen letztendlich alle Krallen an allen Pfoten. Bei zwölf Hunden wurde ein Wiederauftreten einer Onychomadese beobachtet. Es bestand kein relevanter Zusammenhang zwischen Geschlecht, Art des Wohnens, dem Futter und dem Gesundheitsmanagement, dem physischen Stress und der Entwicklung von SLO mit Ausnahme des Alters, ab welchem eine intensivere Bewegung begann. Die am häufigsten verwendete Kombinationstherapie bestand aus essentiellen Fettsäuren, Pentoxifyllin und Tetrazyklin; eine Verbesserung trat bei 17 Tieren auf. Kalzium, Natrium und Phosphor Konzentrationen waren in den Krallen betroffener Hunde höher, während die Zinkkonzentrationen niedriger waren. Der Mineralgehalt der Haarproben der betroffenen Hunde war von jenem der Kontrollhunde nicht signifikant verschieden. Schlussfolgerung und klinische Bedeutung: Die symmetrische lupoide Onychomadese beim Bearded Collie ist klinisch jener Erkrankung ähnlich, die bei anderen Rassen in Bezug auf klinische Zeichen und Behandlungserfolg beschrieben wurde. Eine sehr frühzeitige anstrengende Aktivität könnte das Risiko eines Auftretens der Erkrankung bei dieser Rasse fördern. 要約: 背景: 対称性ループス状爪脱落症(SLO)は、ドイツのベアデッド・コリーにしばしば認める疾患である。 目的: 本研究の目的は、SLOのベアデッド・コリーの動物栄養食事療法学会/ LMUミュンヘンからの歴史的および臨床的データ、ならびに毛髪および爪のミネラル含有量を正常対照犬と比較することであった。 被験動物: 28頭の罹患ベアデッド・コリーと39頭の対照犬。 材料と方法: オーナーは、育て方、環境条件および食事療法に関して広範なアンケートに回答した。爪標本は、爪のトリミングまたは紛失した爪の収集によって得られた。体のいくつかの領域から抜毛することによって毛サンプルを得た。サンプルを灰に変換し、原子吸光分光光度計で評価した。 結果: 罹患犬の臨床徴候は結局四肢のすべての爪に伴った。 12頭の犬において爪脱落症の再発が観察された。より激しい運動が始まった年齢を除いて、性別、住居、食事および健康管理、身体的ストレスとSLO発症との間に関連性はなかった。最も一般的に使用されている治療の組み合わせは、脂肪酸、ペントキシフィリンおよびテトラサイクリンであった。17頭の動物で改善を認めた。カルシウム、ナトリウムおよびリン濃度は罹患犬の爪においてより高かったが、亜鉛濃度はより低かった。罹患犬の毛サンプルのミネラル含有量は、コントロール群とそれほど違いはなかった。 結論と臨床上の重要性: ベアデッド・コリーの対称性ループス状爪脱落症は、臨床的徴候および治療に対する反応に関して他品種に記載されているものと臨床的に類似している。早期の激しい活動は、この品種の疾患発生のリスクを高める可能性がある。 摘要: 背景: 对称性狼疮样脱甲症(SLO)是一种在德国的长须牧羊犬中并非偶见的疾病。 目的: 本研究资料来自慕尼黑大学动物营养和饮食研究所, 目的是比较患SLO的长须牧羊犬和对照犬的病史和临床症状, 以及毛发和爪的矿物质含量。 动物: 二十八只患SLO的长须牧羊犬和三十九只对照犬。 方法和材料: 由主人填写关于抚养、环境条件和饮食的广泛调查问卷。通过修剪爪子或脱落的爪子获得爪样本; 从身体的多个部位采集毛发; 将样品转化为灰分, 并在原子吸收分光光度计中测定。 结果: 患犬爪部的所有爪子最终都会有临床症状。十二只犬中出现了脱甲症的复发。除了早期更剧烈运动的年龄外, 性别、饲养场所、饮食、健康管理、身体压力和SLO的发展之间没有关联。最常用的治疗组合是脂肪酸、己酮可可碱和四环素; 17只动物的临床症状得到了改善。患犬爪中的钙、钠和磷浓度较高, 而锌浓度较低。患犬毛发样本的矿物质含量与对照无显着差异。 结论和临床价值: 在临床症状和治疗效果方面, 长须牧羊犬的对称性狼疮样脱甲症与其他品种所描述的相似。早期剧烈活动可能会增加该品种的发病风险。 Resumo: Contexto: A onicomadese lupoide simétrica (SLO) é uma doença não raramente vista em bearded collies na Alemanha. Objetivos: O objetivo deste estudo foi comparar dados clínicos e de prontuários, bem como o conteúdo mineral dos pelos e uhas, entre bearded collies com SLO e cães normais controle, no Instituto de Nutrição Animal e Dietética/LMU Munique. Animais: Vinte e oito bearded collies afetados e 39 cães controle. Métodos e materiais: Os proprietários preencheram um extenso questionário sobre educação, condições ambientais e dieta. Espécimens de unhas foram obtidos por corte de unhas ou coleta de unhas perdidas; os pelos foram obtidos por arrancamento de amostras de diversas áreas corpóreas; as amostras foram transformadas em cinzas e avaliadas em um espectrofotômetro de absorção atômica. Resultados: Eventualmente, os cães afetados apresentavam envolvimento de todas as unhas em todas as patas. Em doze cães, observou‐se recorrência da onicomadese. Não houve associação relevante entre gênero, habitação, dieta e rotina de saúde, estresse físico e o desenvolvimento de SLO, com exceção da idade em que o animal começou a praticar exercícios mais intensos. A associação de tratamentos mais utilizada foi ácidos graxos, pentoxifilina e tetraciclina; houve melhora em 17 animais. As concentrações de cálcio, sódio e fósforo foram maiores nas unhas dos animais afetados, enquanto as concentrações de zinco foram menores. Não houve diferença significativa entre o conteúdo mineral dos pelos dos animais afetados e controle. Conclusões e importância clínica: Em relação aos sinais clínicos e resposta ao tratamento, a onicomadese lupoide simétrica em bearded collies é clinicamente similar ao que tem sido descrito em outras raças. A prática de atividades extenuantes precocemente pode aumentar o risco dessa doença em animais desta raça.